Free software and its legal implications (2011)
The article analyses two traditional arguments which the spanishauthors have maintained against the compensation for nonpecuniary loss in the Law of Contract: First, in the Civil Codethe precepts about contractual liability refer only to pecuniaryloss. Second, the classic concept of non pecuniary-loss, which isalways connected to personality rights. This research makes acritical analysis to the main jurisprudential line on this subject,which allows compensation for non-pecuniary loss without anyrestriction. We propose two criteria: damages for non-pecuniaryloss which result from breach of contract can be compensatedonly if they are important and foreseeable for the debtor